Pengaruh Latihan Mallet Beban Terhadap Pukulan Jarak Jauh Atlet Woodball Kabupaten Musi Rawas Utara - Syafutra, Wawan; Remora, Hengky (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to find out whether weight mallet training can have a significant effect on long-distance hitting in woodball athletes in North Musi Rawas Regency. This study is an experimental research with a research design using a one-group pretest-posttest design. The total sampling technique with the number of samples is 15 people who are woodball athletes of North Musi Rawas Regency. The procedures for this experimental research are: (1) initial test (2) treatment administration, (3) final test. Based on the results of the T test, the P value (sig.) is 0.030 < 0.05. This result shows that there is a singnifikan effect after being given weight mallet training on the long-distance hitting of woodball athletes in North Musi Rawas Regency